B-H⋯π and C-H⋯π interactions in protein-ligand complexes: carbonic anhydrase II inhibition by carborane sulfonamides - Fanfrlík, Jindřich; Brynda, Jiří; Kugler, Michael; Lepšík, Martin; Pospíšilová, Klára; Holub, Josef; Hnyk, Drahomír; Nekvinda, Jan; Grüner, Bohumír; Řezáčová, Pavlína (Physical chemistry chemical physics, 2023)
Among non-covalent interactions, B-H⋯π and C-H⋯π hydrogen bonding is rather weak and less studied. Nevertheless, since both can affect the energetics of protein-ligand binding, their understanding is an important prerequisite for reliable predictions of affinities. Through a combination of high-resolution X-ray crystallography and quantum-chemical calculations on carbonic anhydrase II/carborane-based inhibitor systems, this paper provides the first example of B-H⋯π hydrogen bonding in a protein-ligand complex. It shows that the B-H⋯π interaction is stabilized by dispersion, followed by electrostatics. Furthermore, it demonstrates that the similar C-H⋯π interaction is twice as strong, with a slightly smaller contribution of dispersion and a slightly higher contribution of electrostatics. Such a detailed insight will facilitate the rational design of future protein ligands, controlling these types of non-covalent interactions.
Keywords: Sulfonamides; Carbonic Anhydrase II; Crystallography, X-Ray; Ligands; krystalografie rentgenová; karboanhydrasa II; sulfanilamid; Sulfanilamide; sulfonamidy; ligandy